Predicting physiological capacity of human load carriage – A review. (January 2016) - Drain, Jace; Billing, Daniel; Neesham-Smith, Daniel; Aisbett, Brad
Abstract: This review article aims to evaluate a proposed maximum acceptable work duration model for load carriage tasks. It is contended that this concept has particular relevance to physically demanding occupations such as military and firefighting. Personnel in these occupations are often required to perform very physically demanding tasks, over varying time periods, often involving load carriage. Previous research has investigated concepts related to physiological workload limits in occupational settings (e.g. industrial). Evidence suggests however, that existing (unloaded) workload guidelines are not appropriate for load carriage tasks. The utility of this model warrants further work to enable prediction of load carriage durations across a range of functional workloads for physically demanding occupations. If the maximum duration for which personnel can physiologically sustain a load carriage task could be accurately predicted, commanders and supervisors could better plan for and manage tasks to ensure operational imperatives were met whilst minimising health risks for their workers. Highlights: Physiological limits in occupational settings have previously been investigated. Existing workload limit guidelines are likely not appropriate for load carriage. A model to predict occupational load carriage performance has been proposed. Able to provide rapid assessments to inform task and personnel management. The predictive tool would be invaluable for planning in military and firefighting.